Law And Legal Theory - DE1048 - 202302 - Mac Lean Martins, Ana Cecilia María (2023)
In this course, we will explore a number of controversial United States Supreme Court cases that were decided under the Bill of Rights and the Fourteenth Amendment requirements of due process and equal protection. Our aim will be to consider not only these cases but the important questions they raise about how to interpret the Constitution and adjudicate constitutional cases. What is the role of the original meaning of the Constitution and of the constitutional text in constitutional interpretation and adjudication? In what sense, if any, is the U.S. Constitution a living constitution? What is the role of contemporary ideas in interpreting the Constitution? What role, if any, do moral principles play? Is the original Constitution, as some legal theorists have claimed, lost and in need of restoration? What might that mean? How ought we to go about choosing among constitutional theories? Might some theories be more compatible with the rule of law and the function of a constitution? With the content of a particular constitution? With morality? We will consider these and other theoretical questions as we examine the Supreme Court¿s principal decisions regarding contraception, abortion, assisted suicide, marriage, homosexuality, and individual gun ownership.